The Role of West Javanese Traditional Musical Instruments to Attract Visitors at the West Java Pavilion - Pradini, Gagih; Kusumaningrum, Anisa Putri; Agustiani, Fitri; Putri, Ananda Amelia; Suroto, Alip; Suwandojo, Dodik Prakoso Eko Hery (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Taman Mini Indonesia Indah is one of the recreational destinations for the people of Indonesia, especially Jakarta. The purpose of the establishment of the mini park is as a place for the younger generation of Indonesia to get to know the various tribes, customs and religions in Indonesia through various regional platforms and museums. West Java Provincial Anjungan is one of the Regional Anjung in Taman Mini Indonesia Indah. West Java's traditional musical instruments play an important role as a cultural heritage that has been preserved for centuries and used in various traditional events and ceremonies. This research uses qualitative research methods and observation. This research aims to get a general understanding from the participant's point of view. The data collection techniques used are: Observation is a researcher going directly to the West Java Anjungan, using the Interview method with the manager of the West Java Anjungan and documentation techniques to collect data. West Java musical instruments do not have similar characteristics. Traditional West Javanese musical instruments play an important and irreplaceable role in the lives of West Javanese people. But for the role of musical instruments in the West Java platform in attracting visitors does not really work according to its purpose. Visitors are only interested in coming to the West Java platform if certain events are held, which of course in the event the West Java musical instruments participate as accompaniment